Making the Most of Structural Support: Moderating Influence of Employees' Clarity and Negative Affect - Parker, Sharon K.; Johnson, Anya; Collins, Catherine; Nguyen, Helena (Academy of Management Journal, 2013)
We investigated structural support as a work design characteristic potentially enabling employee effectiveness in demanding contexts, proposing that structural support enhances job and role outcomes for employees but that effects depend on both the outcome under consideration (job vs. role) and the employees themselves. We tested hypotheses in a within-persons quasi-experiment in which 48 hospital doctors carried out their work with and without structural support. Structural support had positive effects on perceived core job performance, and these effects were stronger for individuals with higher clarity about others' work roles, suggesting that individuals can better mobilize available support when clear about how to allocate it. Support was also associated with improved role outcomes although, consistently with conservation of resources theory, effects differed with affect. For individuals with higher negative work affect, structural support was associated with lowered perceived role overload (a resource protection mechanism). For individuals with lower negative work affect, support was associated with higher perceived skill utilization and proactive work behavior (a resource accumulation mechanism). We approach social support at work in a novel way, extend relational approaches to work design, and show the value of considering both job and role outcomes in work redesign research.